Niektóre aspekty sytuacji i polityki demograficznej Rumunii - Mesaros, Emil (Wydział Prawa i Administracji UAM, 1973)
In the period 1935 - 1938 the birth rate was 30%o, while 180 newborn infants out of 1000 live born ones died during the first year of life. After a period of a significant high birth rate in the 40's and a certain stability in the early 50's a violent decrease in birth rate followed in the years 1956 -1966. It is interesting that this decrease was parallel to the continuously improving economic situation of the country. The decrease in birth rate that had taken place all over Europe occured in Rumania later. It was caused by: an increased professional activity of women, urbanization and migrational movements from rural districts to towns, changed attitudes towards procreation, increased number of divorces and abortions. Since 1966 Romania has started to stimulate the birth rate intensively. The following means of stimulation have to be mentioned: a) State support for children in the form of month allowances; financial help for families with four and more children; after delivery reliefs; b) development of nurseries, kindergartens and so on; c) general reliefs for women with children under seven; d) free medical care for pregnant women and for those with children under two; e) comprehensive free education; f) limitations of abortions (decrees of 26 IX 1966 nad 17 II 1972).
Some Aspects of the Demographic Situation and Demographic Policy in Rumania